Polyvinylidene fluoride membrane coated with titanium dioxide nanofibers for photocatalytic membrane process - Mohamad Nor, Nor Azureen (2016)
Photocatalytic oxidation nowadays has been pledging as the valuable process for air and water purification because of its capability to degrade organic pollutants. Photodegradation of organic pollutants by suspended photocatalyst have major drawbacks in terms of difficulty in post-recovery treatment. In this study, polyvinylidene fluoride (PVDF) nanocomposite membrane consisted of electrospun titanium dioxide (TiO2) nanofibers (PVDF/e-TiO2) was prepared by hot pressing the as-spun TiO2 nanofibers onto PVDF flat sheet membrane. The TiO2 nanofibers acted as a photocatalyst, while PVDF membrane acted as a support. The hot press technique was carried out by applying heat at 100 °C, 160 °C and 180 °C for 30 minutes. The nanocomposite membranes were characterized by field emission scanning electron microscopy (FESEM), energy dispersive x-ray spectrometry (EDX), differential scanning calorimetry and UV-vis-near-infrared spectroscopy. The FESEM images and EDX analysis showed good adhesion and dispersion of TiO2 nanofibers in the PVDF membrane. Nanocomposite membrane prepared at hot pressing temperature of 100 °C (PVDF/e-TiO2-100) exhibited appropriate morphological structure and physical properties. PVDF/e-TiO2-100 exhibited the highest photocatalytic activity in the degradation of bisphenol A (BPA) under UV irradiation compared to the PVDF/e-TiO2-160 and PVDF/e-TiO2-180 with degradation rate of 84.53 %, 77.61 % and 62.54 %, respectively. Meanwhile, the pure water flux was reduced as the hot press temperature increased; 15.79 L/m2.h (100 °C), 14.80 L/m2.h (160 °C), 8.88 L/m2.h (180 °C). However, the BPA rejection of the PVDF/e-TiO2-100 was found to be the lowest among the prepared nanocomposite membranes. Based on the obtained results, it can be concluded that a fine-tuning on the optimization study of the membrane pore size by several approaches is required in order to ensure the developed PVDF/e-TiO2 membranes can be efficiently functioned by means of photodegradation and filtration applications.